First validation of the gout activity score against gout impact scale in a primary care based gout cohort - La-Crette, Jonathan; Jenkins, Wendy; Fernandes, Gwen Sascha; Valdes, Ana M.; Doherty, Michael; Abhishek, Abhishek (Elsevier, 2017)
Objectives To validate the gout activity score (GAS) against the gout impact scale in a primary care based gout cohort. Methods This was a single-centre cross-sectional study. People with gout who participated in previous research at Academic Rheumatology, University of Nottingham, UK, and consented for participation in future studies were mailed a questionnaire in September 2015. Those returning completed questionnaires were invited to attend for a study visit at which blood was collected and musculoskeletal examination was performed. The Gout Assessment Questionnaire, which contains the gout impact scale (GIS), and short form (SF) 36v2 questionnaires were completed. The GAS3-step-c score was calculated. Spearman’s correlation coefficient was calculated to examine correlation between GAS and SF-36 v2, and GIS. Statistical analyses were performed using PASW v22. Results 102 (93% men) of the 150 participants who were mailed a questionnaire attended the study visit. Their mean (SD) age, BMI, serum uric acid and GAS were 67.94 (9.93) years, 29.96 (4.57) kg/m2, 5.25 (1.75) mg/dl, and 2.99 (0.74) respectively. There was moderate correlation between GAS and gout concern overall, unmet gout treatment need, and gout concern during an attack components of GIS (r= 0.306 to 0.453), but no to poor correlation between GAS and summary scores and scales of SF-36 v2 (r= -0.090 to -0.251). Conclusion This first study to validate GAS against the GIS found moderate correlation. However, this study did not examine the predictive validity of GAS, and prospective studies are needed before GAS can be used widely.